1998
DOI: 10.1046/j.1523-1747.1998.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Plasminogen Activator Inhibitor Type 2 (PAI-2) in Hair and Nail: Implications for Terminal Differentiation

Abstract: Plasminogen activator inhibitor type 2 (PAI-2) is an unusual serine proteinase inhibitor in that it is largely retained within the cell and is found in high concentrations in the upper viable layers of human epidermis. Studies using transfected cell lines that express high levels of PAI-2 have suggested that this inhibitor may confer protection against programmed cell death. To test the hypothesis that PAI-2 may protect epithelial cells in vivo from premature programmed cell death, we determined expression pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 31 publications
5
30
0
Order By: Relevance
“…Recent studies of PAI-2 gene expression have suggested that this protein may be required for specific steps in hair and skin development in the mouse (41). It is also a major component of the heavily cross-linked cornified envelope formed during the final stages of epidermal keratinocyte differentiation (42).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of PAI-2 gene expression have suggested that this protein may be required for specific steps in hair and skin development in the mouse (41). It is also a major component of the heavily cross-linked cornified envelope formed during the final stages of epidermal keratinocyte differentiation (42).…”
Section: Discussionmentioning
confidence: 99%
“…The shared expression of K6 by the companion layer and the niche has led to the investigation of potential similarities and differences among these populations of cells and raised the issue of whether there is a shared lineage relationship (Higgins et al, 2009). In fact, K6-expressing cells in telogen and anagen, as well as the cells surrounding the club hair in catagen, share a common molecular signature [expression of K6 (Winter et al, 1998;Wang et al, 2003;Hsu et al, 2011), PAI-2 (Lavker et al, 1998), calretinin (Poblet et al, 2005) and S100A6 (Ito and Kizawa, 2001)]. The companion layer is composed of thin long cells adjacent to the IRS, whereas the K6 + niche (and catagen K6 + ) cells are cuboidal (Hsu et al, 2011).…”
Section: Hopx Expression Defines a Previously Unrecognized Progenitormentioning
confidence: 99%
“…The K6 + layer is thought to share similarities with segments of the companion layer of anagen HFs (Higgins et al, 2009); both are adjacent to the ORS and express K6 (Winter et al, 1998;Wang et al, 2003;Hsu et al, 2011), plasminogen activator inhibitor 2 (PAI2) (Lavker et al, 1998), calretinin (Poblet et al, 2005) and S100 calcium-binding protein A6 (S100A6) (Ito and Kizawa, 2001). However, the lineage relationship between the K6 + inner bulge and companion layers remains a mystery.…”
Section: Introductionmentioning
confidence: 99%
“…RNA probes were prepared using 35 S-labeled UTP. In situ hybridization was conducted as described (24).…”
Section: Northern Blot Hybridization-poly(a)mentioning
confidence: 99%